PENGARUH STRES KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI ERA NEW NORMAL - Julfandika, Raihan; Irawanto , Dodi Wirawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effects of job stress and leadership on the performance of micro, small, and medium-sized tourism enterprise’s employees in Bali Province. This quantitative explanatory study focuses on explaining the relationship between job stress (X1), leadership (X2), and employee performance (Y). Using purposive sampling technique, 52 employees of tourism-sector businesses were selected as the respondents, to whom questionnaires were distributed to harvest the required data. The research instruments were assessed using validity and reliability tests. Here the classical assumption test and the multiple linear regression were performed in SPSS version 20. This study finds that job stress negatively and significantly influences employee performance and that leadership positively and significantly affects employee performance. These facts indicate that an increase in job stress can reduce employee performance and that upgrades in leadership enhance employee performance in the context of tourism enterprises in Bali Province.